2022
DOI: 10.1111/hsc.13814
|View full text |Cite
|
Sign up to set email alerts
|

Association between change in social participation and improved cognitive function among older adults in China: A national prospective cohort study

Abstract: We aimed to assess the association between change in social participation and long‐term improved cognitive function among older adults. Data were obtained from 9648 participants aged ≥60 years in the 2011, 2014 and 2018 waves of the Chinese Longitudinal Healthy Longevity Survey, a national prospective cohort study. Cox regression models were used to calculate adjusted risk ratios (aRRs). Social participation was increased in 20.5% of the participants, decreased in 37.8% of the participants and stable in 41.7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies have attempted to classify social participation, but there is a certain degree of overlap in these classi cations. For instance, some researchers have de ned social participation as encompassing three types: participation in organized social activities, collective leisure activities, and informal social activities (Wang et al, 2022) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have attempted to classify social participation, but there is a certain degree of overlap in these classi cations. For instance, some researchers have de ned social participation as encompassing three types: participation in organized social activities, collective leisure activities, and informal social activities (Wang et al, 2022) [15].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between social participation and cognitive function needs to be clari ed, and there are differences in opinions among different scholars. Some scholars have pointed out that social participation has a positive impact on the cognitive function of older adults (Park, et al, 2022;Wang et al, 2022) [14,15]. Studies have found that older adults who participate in activities have better cognitive function compared to those who do not participate (Zhou et al, 2020) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Older adults have the ability to learn, but the question of how to encourage them to participate actively in learning activities is an important issue for an ageing society. Wang (2010) noted that participation in education is the most basic form of social participation. Apparently, learning is a good way to help older adults avoid social isolation and strengthen their interpersonal networks.…”
Section: Discussionmentioning
confidence: 99%